PENGARUH KEADILAN DISTRIBUTIF DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR YANG DI MODERASI OLEH KOMITMEN ORGANISASI - Fitriani Asis; Aji Ratna Kusumah; Nanok Fitriyadi; Rizkiawan (Program Studi Manajemen, 2026)
The purpose of this study is to examine, analyze, and test the effects of distributive justice and transformational leadership on organizational citizenship behavior among civil servants in the Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu East Kutai Regency, and to examine,. Additionally, to identify, analyze, and test organizational commitment as a moderating variable in the relationship between distributive justice and transformational leadership and organizational citizenship behavior among civil servants in the Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu East Kutai Regency. The population and sample for this study consist of all civil servants in the Investment Promotion and One-Stop Integrated Service Agency of Kutai Timur Regency, totaling 98 employees . The entire population was used as the sample; thus, the sample size for this study is 98 employees. The analysis was conducted using the Smart PLS software. The results of the study indicate that distributive justice and transformational leadership have a positive and significant effect on the organizational citizenship behavior of employees at the Investment and One-Stop Integrated Service Agency of East Kutai Regency. The results also show that the organizational commitment variable moderates the relationship between distributive justice and transformational leadership on organizational citizenship behavior Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu East Kutai Regency